The Flywheel Effect of Gender Role Expectations in Diverse Work Groups - van Dijk, Hans; van Engen, Marloes L. (Frontiers in Psychology, 2019)
Popular press suggests that gender diversity benefits the performance of work groups. However, decades of research indicate that such performance benefits of gender diversity are anything but a given. To account for this incongruity, in this conceptual paper we argue that the performance of gender-diverse work groups is often inhibited by self-reinforcing gender role expectations. We use the analogy of a flywheel to illustrate how gender role expectations tend to reinforce themselves via three mechanisms. Specifically, we argue that gender role expectations shape (a) the allocation of jobs, tasks, and responsibilities, (b) the behavior of perceivers, and (c) the behavior of target women and men. In turn, these three consequences of gender role expectations tend to confirm the initial gender role expectations, thus creating an automatic, self-reinforcing flywheel effect. Such self-reinforcing gender role expectations provide superficial impressions of individual women and men’s actual knowledge and abilities at best. We therefore further propose that each of the three mechanisms of the flywheel of gender role expectations negatively affects group performance to the extent that gender role expectations inaccurately capture group members’ actual knowledge and abilities. Because the extent to which work group members rely on gender role expectations depends on how they form impressions of others, we propose that individuals’ motivation to form accurate impressions is crucial for inhibiting the flywheel of gender role expectations. We close by advancing an agenda for future research on each of the three areas of interest in our conceptual analysis: the flywheel effect of gender role expectations, the consequences of this flywheel effect for group functioning, and ways to motivate group members to form accurate impressions.